Morphological and Structural Characterization of Pineapple Leaf Fibers: Implications for Eco-Friendly Textile Applications - Ahmad Darmawi; Sih Parmawati; Nurfadilah Ikhsani; Fahad (Postgraduate, University of Mataram, 2025)
Natural fibers from pineapple leaves (Ananas comosus L.) are a potential renewable resource, but their characteristics are highly dependent on their geographical origin. This study aimed to characterize the physico-mechanical properties and morphology of pineapple leaf fibers (PALF) sourced from local farmers in Kediri, East Java. Characterization was conducted at an accredited testing institution using SNI standards, covering fineness, bundle tenacity, and Scanning Electron Microscopy (SEM) observations. The results revealed that the fibers exhibited an average fineness of 33.7 dtex and a tenacity of 23.20 g/tex. Morphological analysis showed a course, multi-cellular, and dense fiber structure. Based on these findings, it is concluded that these PALF demonstrate greater potential for applications in technical textiles and as reinforcement in bio-composite materials rather than as a raw material for apparel yarn.